Introducing Practical Theology to English Canada - Couture, Pamela D. (Toronto journal of theology, 2013)
This introduction relates The Wiley-Blackwell Companion to Practical Theology to a network of theologians of theology in Canada and abroad. It notes that practical theology has linkages with English- French-speaking Canadians in the "Narrativity, Identity, and Diversity Seminar," with the program unit of the American Academy of Religion, and with similar academic societies in Ireland, England, and South Africa.